1970
DOI: 10.2307/2258285
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Plant Growth and Distribution in Relation to Waterlogging: I. The Survival of Erica Cinerea L. and E. Tetralix L. and Its Apparent Relationship to Iron and Manganese Uptake in Waterlogged Soil

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Ecology. INTRODUCTIONBannister's study of Erica cinerea and E. tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 17 publications
(7 reference statements)
7
52
1
1
Order By: Relevance
“…oleifolia when grown in soil culture and that this differential response corresponds to the ecology of the two species, S. cinerea heing found in generally wetter habitats. Large amounts of iron were accumulated in the leaf tissues of waterlogged S. caprea and the plants showed symptoms similar to those previously identified as iron toxicity in Erica cinerea (Jones & Etherington, 1970;Jones, 1971a,h). Assimilation of ^^COg by leaf discs showed that photosynthetic potential was much reduced by waterlogging m S. caprea but unaffected in 5. cinerea.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…oleifolia when grown in soil culture and that this differential response corresponds to the ecology of the two species, S. cinerea heing found in generally wetter habitats. Large amounts of iron were accumulated in the leaf tissues of waterlogged S. caprea and the plants showed symptoms similar to those previously identified as iron toxicity in Erica cinerea (Jones & Etherington, 1970;Jones, 1971a,h). Assimilation of ^^COg by leaf discs showed that photosynthetic potential was much reduced by waterlogging m S. caprea but unaffected in 5. cinerea.…”
Section: Introductionsupporting
confidence: 72%
“…caprea and in the previous study with E. cinerea (Jones & Etherington, 1970;Jones, 1971a,b) caused leaf discolouration followed by leaf desiccation and death or abscission. This suggests that iron toxicity may be a main cause of waterlogging injury in those plants which survive the early stages of flooding which are so damaging or lethal to species such as Pisum sativum (Jackson, 1979) or Chamerion angustifolium (Etherington, 1984).…”
Section: Iron Content Of Fe'^'^-treated Plantsmentioning
confidence: 69%
See 1 more Smart Citation
“…Many studies have shown adaptive physiological difference between species that grow in waterlogged soils and those which are intolerant of soil flooding (e.g. H. E. Jones & Etherington, 1970;R. Jones & Etherington, 1971;H.…”
Section: Introductionmentioning
confidence: 99%
“…This species is associated with waterlogged soil conditions (Jones & Etherington, 1970) and is widespread but found at low abundance on degraded cutover bogs (M. McCorry, pers. comm.).…”
Section: Discussionmentioning
confidence: 99%